Atuação cotidiana do farmacêutico na atenção primária à saúde Fortaleza - Maciel, Ana Paula Pessoa (2018)
The pharmacist's role in Primary Health Care must be bui lt through holistic care in a reconstructive and ontological way, overcoming the overvaluation of technical and bureaucratic know how centered on the drug, but considering the user as having a historical and of self knowledge, bringing this and articulatin g with himself and the other members of the team possibilities for extended care. This thesis aimed to understand the performance of the pharmacist in his daily praxis with a view to an integration in Primary Health Care in the Municipality of Fortaleza. T he methodological strategy carried out in the present thesis was developed in the field of qualitative approach. The subjects that participated in the research were: pharmacists, other health professionals and managers. Data were collected through semi str uctured interviews and a focus group. The analysis of the results was established through hermeneutics and the dialectic, originated four essential categories: Description of the performance of the pharmacist in the PHC; Identification of pharmaceutical pr actices in the team; The view of pharmacists related to their practices in PHC; The view of other health professionals related to PHC practices in PHC; The managers 'view regarding PHC practitioners' practices; Pharmaceutical practices in PHC: Factors that facilitate and hinder the integration of the pharmacist in the team; Perspective to integrate the pharmacist into PHC. Primary Health Care refers to a dynamic space that needs to be integrated with the health team and not be reduced to the dispensation o f medicines. It is imperative that the 'health' of this professional be diverted from the focus of the prescription and medication to focus on the pharmacotherapeutic follow up and interdisciplinary actions of promotion and health education. The inclusion of the pharmacist in integral, coordinated, yet continuous, safe care remains a challenge. It was possible to understand that pharmacists do not demonstrate a plausible understanding of interdisciplinarity as a necessary part for the implementation of inte gral work with the community, not glimpsing the actions that guarantee the bond, accessibility and continuity of care as an essential part of their work, not thus perceiving themselves as members of an integrated team.